Proyecto de creación de una empresa comercializadora y exportadora de bisuteria y adornos artesanales ecuatorianos, promoviendo el comercio equitativo - Romero Santana, Ileana María (2010)
Daily creative craftsmen work fard for obtaining high-quality final products. Unfortunately, their efforts made are not well-appreciated in our country.